An Investigation of School Resource and Safety Programs Policy and Practice in Virginia, 2016-2019 ([Verlag nicht ermittelbar], 2023)
This study seeks to inform about the effectiveness and impact of school safety programs in the state of Virginia. In many Virginia schools, ensuring school safety often involves the use of School Resource Officers (SRO) and School Security Officers (SSO), or some combination of SROs and SSOs. This study investigated the current state of SRO and SSO programs in Virginia to illuminate how SRO and SSO programs are operating and uncover best practices associated with program development, implementation, and evaluation. Specifically, the research questions were: RQ1: How are SROs and SSOs trained to operate in K-12 public schools in the Commonwealth of Virginia? RQ2:What are the criteria that are being used to select SROs and SSOs to operate in schools? RQ3: How are the activities of SROs and SSOs that do not result in an arrest being documented? RQ4: How are SROs and SSOs operating in schools supervised by their own department and/or by the school(s) in which they operate? RQ5: What criteria are used to assess SRO and SSO performance? RQ6: To what extent are SROs and SSOs involved addressing school disciplinary matters that do not rise to the level of criminal activity? RQ7: Are there differences when comparing between school districts that have MOUs with local law enforcement, and school districts that do not have formal arrangements with local law enforcement?